Relationship Of Ship Sanitation With The Existence Of Cockroach Vectors In Passengers In Tanjung Perak Surabaya Port - Olievia Hapshari Putri, Nadya; Herdiani, Novera (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
The ship is a small community consisting of various passengers. Opportunities for passengers interact with each other, and various foods or drinks, as well as various public facilities are very likely to occur. Pandemics that occur are caused by poor sanitation, such as ventilation, inadequate ship lighting, poor hygiene, food contaminated with viruses, scattered waste that is not disposed of in trash bins, and the lack of medical personnel is thought to be the cause of the outbreak. The purpose of this study was to analyze ship sanitation with the presence of cockroach vectors on passenger ships at the Port of Tanjung Perak Surabaya. The type of research used in this research is observational analytic with cross sectional approach. The population of the researchers is that all passenger vessels leaning on Surabaya’s Tanjung Perak Port are 40 ships. The research sample was taken by simple random sampling with a sample of 36 ships. Analysis of the data used is chi-square. Data analysis showed a relationship between ship sanitation and the presence of cockroach vectors on passenger ships with a value of 0.00 <0.05. The results showed that ship sanitation showed a large proportion (61.1%) of low risk of the source of transmission of the disease so that it could improve the health status of passengers. The existence of cockroach vectors showed that most (66.7%) were not found so as not to increase the spread of a disease due to cockroach vectors. The conclusion in this study is that there is a relationship between ship sanitation and the presence of cockroach vectors. The advice given is to improve inspection of ship sanitation regularly by officers of the Class I Surabaya KKP Tanjung Perak Region.